Non-neoplastic pathologies mimicking sarcoma – Experience from a tertiary referral centre multidisciplinary team. Issue 156 (November 2022) - Ahmed Malik, Faheem; Roy Chaudhary, Snehansh; Edwards, Nathan; Rajasekaran, Raja Bhaskara; Chari, Basavaraj
Highlights: 8.6% of referrals to our sarcoma MDT were non-neoplastic pathologies. Most tumour-mimics were vascular or inflammatory conditions. The most common diagnosis was vascular malformation. Non-neoplastic conditions can radiologically mimic sarcoma in a number of ways. Abstract: Objective: Distinguishing non-neoplastic tumour-mimicking pathologies from bone and soft tissue tumours is one of the fundamental aims of a tertiary centre sarcoma multidisciplinary team (MDT) service. In this study, we aim to analyse the incidence of non-neoplastic lesions referred to a tertiary referral service as suspected sarcoma, and to analyse the spectrum of conditions comprising these tumour-mimicking pathologies. Materials and methods: We conducted a retrospective observational study compiling the biopsy-proven non-neoplastic outcomes of suspected sarcoma cases referred to our MDT in the last year. We identified all referrals made to our service between 1st January 2020 and 31st December 2020 and compiled their histological diagnoses. Results: A total of 976 new cases were referred to our MDT as suspected sarcoma in one year. Of these referrals, 8.6% (84/976) received a biopsy-proven outcome of non-neoplastic pathology. These non-neoplastic outcomes were categorised into the following types of pathology: 32.1% vascular, 31.0% inflammatory, 14.3% traumatic, 6.0% degenerative, 6.0% idiopathic, 4.8% infective, 3.6% metabolic, 1.2% autoimmune, and 1.2% genetic. Conclusion: A significant proportion of pathologies referred to a tertiary centre sarcoma MDT are non-neoplastic in nature. These lesions are made up of a range of pathologies, with vascular and inflammatory conditions being the most common. Our study, the first of its kind, offers clinicians an insight into tumour-mimicking pathologies encountered by a tertiary centre.